Bibliometric Analysis of Towards Development Teaching and Learning Based on 3D Animation - Aas Nuraisah; Aina Febri Andini (Westscience Press, 2023)
Learning is the process by which a person acquires new knowledge, ability, understanding, or experience through interaction with information, teachers, the environment, or their own learning experiences. In addition, its learning methods are not always relevant and are often monotonous, causing students to be bored, uninvolved or unmotivated during the learning process. This can lead to difficulty understanding and retaining the subject matter. Animated 3D-based learning has become one of the increasingly popular modern educational methods to overcome monotonous learning. This method combines 3D animation technology with the learning process to create an interactive and engaging learning environment. The concept, advantages and disadvantages of 3D animation-based learning are discussed in this article. In addition, we describe some case studies that demonstrate the use of this method in education, both in schools and in various learning institutions. 3D animation-based learning offers a new opportunity to improve students ' understanding of difficult concepts by presenting the subject matter in a more visual and tangible form. The use of 3D animation in learning has great potential to improve the effectiveness of the learning process, research and development in this area can help maximize the benefits of 3D animation-based learning.